Pendidikan Pencegahan Dan Pengurangan Risiko Bencana (PRB) Sebagai Strategi Ketahanan Sekolah Dasar Dalam Penanggulangan Bencana - Zela Septikasari; Heri Retnowati; Insih Wilujeng (Jurnal Ketahanan Nasional, 2022)
Abstract The aims of this study are to identify (1) the implementation of primary school DRR education in Indonesia, (2) strategies that can be implemented in integrating primary school DRR, and (3) the proposed framework for primary school resilience in disaster management.  The method used in this research was Systematic Literature Review (SLR).  The results showed that the implementation of DRR education in Elementary Schools in Indonesia was carried out through the integration of DRR materials into the curriculum, the integration of DRR materials into local content, and the integration of DRR materials into self-development.  Strategies that can be implemented in integrating primary school DRR education include integration through an online platform created by the Ministry of Education and Culture, involving multi-stakeholders in disaster management in schools, implementing schools independently, integration through scout extracurriculars, through the civil servant pre-service system, and  through local regulatory policies. The proposed framework for primary school resilience in disaster management include: (1) School disaster risk assessment and planning for the integration of DRR Education, (2) Teacher and staff training related to the integration of DRR Education, (3) Implementation of DRR Integration in accordance with school characteristics and taking into account the sustainability of integration, (4) Evaluation of the implementation of DRR Education Integration, and (5) DRR Integration Innovation.